GEOENGINEERING PERIOD REQUIREMENT IN PILGRIMAGE TOURISM - A. Ch. Abdiyev; J. Qosimov (American Journals Publishing, 2024)
This article provides information on geographic information systems and their use in tourism, especially in the field of pilgrim tourism. The authors provide information on the GAT definition and its specifics.
Keywords: GIS, tourism, pilgrim tourism, holy place, information, internet.